Discrete enhancer elements mediate selective responsiveness of Enhancer of split complex genes to common transcriptional activators. - Nellesen, D.T.; Lai, E.C.; Posakony, J.W. (Developmental Biology, 1999)
In Drosophila, genes of the Enhancer of split Complex [E(spl)-C] are important components of the Notch (N) cell-cell signaling pathway, which is utilized in imaginal discs to effect a series of cell fate decisions during adult peripheral nervous system development. Seven genes in the complex encode basic helix-loop-helix (bHLH) transcriptional repressors, while 4 others encode members of the Bearded family of small proteins. A striking diversity is observed in the imaginal disc expression patterns of the various E(spl)-C genes, suggestive of a diversity of function, but the mechanistic basis of this variety has not been elucidated. Here we present strong evidence from promoter-reporter transgene experiments that regulation at the transcriptional level is primarily responsible. Certain E(spl)-C genes were known previously to be direct targets of transcriptional activation both by the N-signal-dependent activator Suppressor of Hairless [Su(H)] and by the proneural bHLH proteins achaete and scute. Our extensive sequence analysis of the promoter-proximal upstream regions of 12 transcription units in the E(spl)-C reveals that such dual transcriptional activation is likely to be the rule for at least 10 of the 12 genes. We next show that the very different wing imaginal disc expression patterns of E(spl)m4 and E(spl)mgamma are a property of small (200-300 bp), evolutionarily conserved transcriptional enhancer elements, which can confer these distinct patterns on a heterologous promoter despite their considerable structural similarity [each having three Su(H) and two proneural protein binding sites]. We also demonstrate that the characteristic inactivity of the E(spl)mgamma enhancer in the notum and margin territories of the wing disc can be overcome by elevated activity of the N receptor. We conclude that the distinctive expression patterns of E(spl)-C genes in imaginal tissues depend to a significant degree on the capacity of their transcriptional cis-regulatory apparatus to respond selectively to direct proneural- and Su(H)-mediated activation, often in only a subset of the territories and cells in which these modes of regulation are operative.